1971
DOI: 10.1111/j.1550-7408.1971.tb03316.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Cryptosporidium wrairi from the Guinea Pig

Abstract: SYNOPSIS. The ultrastructure of the known tissue stages of Cryptosporidium wrairi Vetterling, Jervis, Merrill, and Sprinz, 1971 parasitizing the ileum of guinea pigs is described. Young trophozoites are surrounded by 4 unit membranes, the outer 2 of host origin, the inner 2 the pellicle of the parasite. Each trophozoite contains a vesicular nucleus with a large nucleolus. Its cytoplasm contains ribosomes, but eventually fills with cisternae of the rough endoplasmic reticulum. As the trophozoite matures the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
60
2
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 34 publications
12
60
2
1
Order By: Relevance
“…The ''moving junction'' shown by them was not evident in our observation. Moreover, Iseki (1979) reported that the electron-dense band was formed at the base of the microvillus; the dense band in the present study was similar to the one reported by Vetterling et al (1971).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The ''moving junction'' shown by them was not evident in our observation. Moreover, Iseki (1979) reported that the electron-dense band was formed at the base of the microvillus; the dense band in the present study was similar to the one reported by Vetterling et al (1971).…”
Section: Discussionsupporting
confidence: 80%
“…Vacuolation has also been reported ultrastructurally in Cryptosporidium spp. (Vetterling et al, 1971;Current and Reese, 1986;Lumb et al, 1988;Ostrovska and Paperna, 1990). It is known that the vacuolation occurs as a result of secretion from the micronemes, rhoptries, and dense granules.…”
Section: Discussionmentioning
confidence: 99%
“…Our TEM and LM study documented all C. parvum developmental stages on the surface of the tracheal and bronchial epithelial cells without involvement of lung parenchyma (Meulbroek et al, 1991). These forms were morphologically similar to those described in the intestinal lumen (Vetterling et al, 1971;Pohlenz et al, 1978;Goebel & Braendler 1982;Pearson & Logan, 1983;Lefkowitch et al, 1984;Current & Reese, 1986;Meulbroek et al, 1991). Moreover, the epithelium bea ring the parasitic stages from rats sacrificed at the end of the study protocol did not show progressive histo logic changes, with appearance of an immature malpighian metaplasia, as recently reported by others (Roussel et al, 1995).…”
Section: Discussionsupporting
confidence: 74%
“…As with other irritative stimula, the deciliation process may represent cellular res ponse to parasite adhesion, whereas the nuclear changes and the well-developed RER should be related to an increased protein synthesis, thus possibly making available the proteins needed by Cryptosporidium metabolism (Tadeja-Simborio et al, 1993). The double electron-dense band observed in many parasites may not be a feature typical of tracheal infec tion; this structure, although unusual, was reported also by Vetterling et al (1971) in the intestinal infection caused by Cryptosporidium wrairi. The ultrastructural features observed in our samples, chiefly the absence of severe lesions of the epithelial cells and of the lung parenchyma, support that, as in human cases of respiratory tree localization, Crypto sporidium may be considered as a low virulence res piratory pathogen (Clavel et al, 1996).…”
Section: Discussionmentioning
confidence: 91%
“…This apparently cannot be jus tified in light of existing fine structural data. Epieimerians and microvillar eimerians remain free in the parasitophorous vacuole (Molnar andBaska, 1986, Paperna andLandsberg, 1987 and present study), while Cryptosporidium forms elaborate attachment through specialised structures and organelles to the parasitophorous vacuole wall at its proximal (cytoplasmic) end (Vetterling, Takeuchi andMadden, 1971, Landsberg and. Species of Cryptosporidium moreover differ from all emeriorine coccidia (suborder: Eimeriorina Leger, 1911), in their peculiar, non flagellated microgamete (Vetterling et al, 1971, Iseki, 1979.…”
Section: Discussionmentioning
confidence: 99%